Perbandingan Aplikasi Pupuk Organik Limbah Rumah Tangga dan Fases Sapi (Bos Taurus) dengan Pupuk Kimia - Nengseh, Trisnawati; Jayanti, Emi; Prasidya, Denaya Andrya (Jurnal EnviScience (Environment Science), 2019)
Livestock business has prospects to be developed because of the high demand for livestock products. So far, cow dung in the petiyen village has only been cleaned and thrown away for nothing without further use. One alternative to overcome this problem is to utilize cow manure as organic fertilizer. In addition to the waste generated from cows in general the petiyen community also produces waste from its household activities. Of the 2 types of organic waste in the form of cow waste and household waste will be processed into organic fertilizer which will be applied to rice and corn plants that are widely grown by farmers in Petiyen Village, Solokuro Subdistrict, Lamongan Regency. The purpose of this study was to determine the effect of the use of organic fertilizer on plant growth. This research method is experimental. The results showed that the average plant height was 13 cm for the use of organic fertilizer media only and 12 cm for mixed organic fertilizer and soil media, while for chemical fertilizer media could not grow. Root length on day 9, which uses 13 cm organic fertilizer media and which uses a mixture of organic fertilizer and 10 cm soil. it can be concluded that organic fertilizer affects the growth of green bean plants.